2006
DOI: 10.1021/om060390j
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-Selective C−H Activation of Substituted Benzenes Effected by a Tungsten Alkylidene Complex without Substituent Coordination

Abstract: Gentle thermolysis of the bis(neopentyl) complex Cp*W(NO)(CH2CMe3)2 (1) at 70 °C in various substituted benzenes results in the loss of neopentane and the generation of the transient alkylidene complex Cp*W(NO)(CHCMe3) (A), which subsequently effects single C−H bond activations of the benzenes. These activations exhibit a pronounced selectivity for the C−H linkages ortho to the benzene substituents. Thus, thermal reactions of 1 with C6H5X lead to the preferential formation of the corresponding Cp*W(NO)(CH2CMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The easiest C–H activation occurs from U to give L ′ via the transition state U † , and reductive elimination from L ′ then gives methane and o - 4b by way of R ′ † and R ′ (Scheme ). The rate-determining step is the C–H activation, consistent with the observed isotope effect k H / k D = 3.6. , The selectivity of C–H activation of arenes can be determined by either thermodynamic or kinetic effects. , In the present case, kinetic control is proposed, but we note that the product o - 4b is favored by both kinetic and thermodynamic effects (Figure )…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The easiest C–H activation occurs from U to give L ′ via the transition state U † , and reductive elimination from L ′ then gives methane and o - 4b by way of R ′ † and R ′ (Scheme ). The rate-determining step is the C–H activation, consistent with the observed isotope effect k H / k D = 3.6. , The selectivity of C–H activation of arenes can be determined by either thermodynamic or kinetic effects. , In the present case, kinetic control is proposed, but we note that the product o - 4b is favored by both kinetic and thermodynamic effects (Figure )…”
Section: Resultssupporting
confidence: 77%
“…Several theoretical studies have been made on carbon–hydrogen bond activation of methane or benzene by electrophilic platinum­(II) complexes, ,,,, but there has been little computational work on the selectivity in anisole activation . A DFT study of the isomers of [PtMe­(anisyl)­(NN)] and of the isomers formed by protonation, namely, [PtHMe­(anisyl)­(NN)] + , [PtMe­(anisole)­(NN)] + , and [Pt­(anisyl)­(CH 4 )­(NN)] + , with NN = bipy or DPK, has therefore been carried out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we realized that 1,2-C–H (or 1,2-C–D) activation took place in the thermolysis of the imidazolin-2-iminato-modified dialkyl precursor (Scheme ), , as exemplified by the reaction of V(NAr)(CH 2 SiMe 3 ) 2 [1,3-Ar′ 2 (CHN) 2 CN] ( A ; Ar = 2,6-Me 2 C 6 H 3 ; Ar′ = 2,6- i Pr 2 C 6 H 3 ), in C 6 H 6 (or C 6 D 6 ) in the presence of PMe 3 . We thus demonstrated that an exclusive formation of the phenyl analogues V(NAr)(CH 2 SiMe 3 )(C 6 H 5 )[1,3-Ar′ 2 (CHN) 2 CN] ( C ) by 1,2-C–H (or 1,2-C–D) bond activation of C 6 H 6 (or C 6 D 6 ) with the dialkyl analogue ( A ) takes place via a vanadium(V) alkylidene intermediate, and a subsequent thermolysis in C 6 H 6 (or C 6 D 6 ) afforded the diphenyl complexes V(NAr)(C 6 H 5 ) 2 [1,3-Ar′ 2 (CHN) 2 CN] ( D ). , The corresponding vanadium(V) alkylidene complex B (proposed as a key intermediate in the reaction of the dialkyl analogue in C 6 D 6 or C 6 H 6 ) and vanadium(V) benzyne complex E (assumed as an intermediate in the latter reaction affording the diphenyl complexes) could be isolated from the reaction mixture by trapping with PMe 3 , and their structures were determined by X-ray diffraction analysis…”
Section: Introductionmentioning
confidence: 86%
“…5 Activation at position 4 on o-difluorobenzene, farthest from the fluorine atoms, is contrary to some of our previous research, during which a preference for activation at the o-F position was documented during the activation of fluorobenzene by Cp*W(NO)(Npt) 2 . 20 Indeed, in most cases of C−H activation of fluorobenzenes, the C−H bond ortho to a C−F bond is the favored site for activation. 21−23 This preference has been attributed to a thermodynamic stabilizing effect by the o-F, since the resulting M−C bond is strengthened more by the ortho C−F bond than the C−H bond in the substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%